2017
DOI: 10.3390/ma10010046
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Monitoring of the Interaction between Cement Matrix and Alkaline Silicate Solution in Self-Healing Systems

Abstract: Alkaline solutions, such as sodium, potassium or lithium silicates, appear to be very promising as healing agents for the development of encapsulated self-healing concretes. However, the evolution of their mechanical and acoustic properties in time has not yet been completely clarified, especially regarding their behavior and related kinetics when they are used in the form of a thin layer in contact with a hardened cement matrix. This study aims to monitor, using linear and nonlinear ultrasonic methods, the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…In addition, NDT-UPV has been successfully used investigating the corrosion of mortar and concrete reinforcement [16,17], and in the study of durability of these construction materials [18][19][20][21][22][23][24]. For instance, non-destructive ultrasonic test methods have been used to monitor microcracking in concrete [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, NDT-UPV has been successfully used investigating the corrosion of mortar and concrete reinforcement [16,17], and in the study of durability of these construction materials [18][19][20][21][22][23][24]. For instance, non-destructive ultrasonic test methods have been used to monitor microcracking in concrete [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, non-destructive ultrasonic test methods have been used to monitor microcracking in concrete [24,25]. Ouarabi et al used ultrasonic measurements in self-healing systems to study the kinetics of the recovery thanks to the healing agent performance [21]. They validated the capacity of the ultrasonic techniques to assess microstructural changes in concretes.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the need of a preliminary modal analysis and to address the issue of a proper selection of the excitation frequency, a broadband impulsive excitation could be exploited. Rectangular pulse excitations at various amplitudes were used in [25] when applying the SSM to analyze the behavior of a cracked cementitious mortar in the presence of a thin layer of sodium silicate solution. The damage indicators adopted in [25] were the classical ones of the method, defined in the time domain.…”
Section: Introductionmentioning
confidence: 99%
“…However, the previous research indicated that the crack width that can be healed in such technique is limited to a maximum of 0.1 mm, which is not enough for practical application [ 6 ]. In addition to autogenous healing, cracks may also be automatically closed using a specific healing agent in the cement matrix [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%